Design and realization of battery protection and balancing circuits - Ju, Chengquan (2012)
This report describes a test model design and realization of the battery protection system, and discusses several factors that affect the performance of the battery balancing scheme. From the test results, it is shown that the voltage-based algorithm can be used in the battery bank, which consists of a few identical batteries of similar internal resistance. And even in different unbalanced situations, the charge current has little to do with the balancing time, because it is just closely related with the shunt resistance and the battery specification. Moreover, it is also shown that the shunt resistance has a significant effect on the balancing time when the balancing circuits operate in the flat portion of the voltage versus SOC curve. This means that the balancing circuit with smaller shunt resistance gives a quicker response to the same unbalanced situation, and that the shunt resistance does not change battery voltages very much after batteries are equalized. At the end of the report several studies like reference voltage, high-voltage performance and over-current and over-voltage protection need to be done as part of the recommendation for the future work.